Empowering Muslim Women in the Digital Halal Economy: Inclusion through Innovation and Ethical Entrepreneurship - Halim, Hendra; Amir, Fakhrurrazi; Sari, Meutia Dwi Novita; DM, Burhanis Sulthan; Fonna, Rizki Putri Nurita; Syahriyal, Syahriyal; Khairi, Fitrah; Sari, Nurma (International Journal of Kita Kreatif, 2025)
The rapid expansion of the digital halal economy presents unprecedented opportunities for Muslim women to participate, innovate, and lead within value-driven economic systems. This study explores how digital technologiesparticularly e-commerce platforms, Islamic financial technology (fintech), and social mediahave become powerful tools for inclusion, entrepreneurship, and leadership among Muslim women. Through a qualitative literature-based approach, this research examines the intersection of gender, Islamic values, and digital innovation, revealing how Muslim women are redefining their economic agency while navigating sociocultural, structural, and regulatory challenges. The study identifies key areas of empowerment, such as ethical branding, syariah-compliant business practices, and community-driven mentoring within digital halal ecosystems. It also highlights the barriers posed by digital illiteracy, gender bias, and inadequate policy frameworks. Drawing from academic literature, case studies, and policy analyses, this paper proposes strategic pathways to build a gender-inclusive digital halal economy through education, value-aligned innovation, and ethical leadership. The findings contribute to global discourses on Islamic economics, gender equity, and digital transformation, emphasizing the importance of inclusive economic models that align with both technological advancement and Islamic ethics.